Silencing of let-7b-5p inhibits ovarian cancer cell proliferation and stemness characteristics by Asp-Glu-Ala-Asp-box helicase 19A. Issue 1 (1st January 2021) - Huang, Xiujuan; Dong, Hongxia; Liu, Yang; Yu, Fen; Yang, Shunshi; Chen, Zhen; Li, Jueying
ABSTRACT: The emergence and recurrence of ovarian cancer are associated with ovarian cancer stem cells. For cancer treatment, gene delivery of microbubbles (MB)-mediated microRNA (miRNA) is considered as a promising approach. In this study, our aim is to investigate the effects of MB-mediated let-7b-5p inhibitor on the proliferation and stemness characteristics of ovarian cancer (OVCA) cells. Let-7b-5p inhibitor mediated by MB was prepared (termed MB-let-7b-5p inhibitor), and the effects of MB-let-7b-5p inhibitor and let-7b-5p inhibitor on OVCA cell viability, proliferation and stemness characteristics were investigated. We found that MB-let-7b-5p inhibitor presented a higher transfection efficiency than let-7b-5p inhibitor alone. The inhibitory effect of MB-let-7b-5p inhibitor on OVCA cells was more significant than let-7b-5p inhibitor. Let-7b-5p targeted DEAD (Asp-Glu-Ala-Asp)-box helicase 19A (DDX19A), which was downregulated in OVCA cells. The downregulation of DDX19A reversed the inhibitory effects of MB-let-7b-5p inhibitor on OVCA cells. To sum up, we found that MB-let-7b-5p suppressed OVCA cell malignant behaviors by targeting DDX19A.